5S Ribosomal DNA of Genus Solanum: Molecular Organization, Evolution, and Taxonomy - Tynkevich, Yurij O.; Shelyfist, Antonina Y.; Kozub, Liudmyla V.; Hemleben, Vera; Panchuk, Irina I.; Volkov, Roman A. (Frontiers in Plant Science, 2022)
The genus Solanum is distributed worldwide and comprises about 1200 species, being one of the largest among the high plants. The genus includes numerous agronomically important species such as potato (S. tuberosum), tomato (S. lycopersicum), and eggplant (S. melongena) as well as medical and ornamental plants. The huge genus Solanum is a convenient model for research in the field of molecular evolution, structural and functional genomics. Clear knowledge of the taxonomy of the genus Solanum is required to increase the effectiveness of breeding programs, but the phylogeny of the genus is still not fully understood. The rapidly evolving intergenic spacer region (IGS) of 5S rDNA has been successfully used for inferring interspecific relationships in several groups of angiosperms. Here, combining cloning and sequencing with bioinformatic analysis of the genomic data available in the SRA database, we evaluate molecular organization and diversity of IGS for 184 accessions, representing 137 species of the genus Solanum. It was found that the main mechanisms of the IGS molecular evolution was step-wise accumulation of single base substitution or short indels, while long indels and multiple base substitution (MBS), which arose repeatedly during the evolution were mostly not fixed and eliminated. The reason for this negative selection seems to be association between indels / MBS and pseudogenization of 5S rDNA. The IGS sequences comparison allowed us to reconstruct the phylogeny of the genus Solanum. The obtained dendrogram is mainly congruent with published data: the same major and minor clades were found. However, relationships between these clades and position of some species (S. cochoae, S. macrocarpon, S. spirale) differ from the previous results and require further clarification. Our results show that 5S IGS represents a convenient molecular marker for phylogenetic studies in the genus Solanum. In particular, the simultaneous presence of several structural variants of rDNA in the genome enables the detection of reticular evolution, especially, within the largest and economically most important sect. Petota. The origin of several polyploid species should be reconsidered.